Edge-to-edge transcatheter valve repair of atrial functional mitral regurgitation positively influences atrial pathology. (14th October 2021) - Petrescu, A; Geyer, M; Ruf, T; Hahad, O; Tamm, A; Da Rocha, J; Schnitzler, K; Hell, M; Schmitt, V; Kreidel, F; Muenzel, T; Von Bardeleben, R S
Abstract: Introduction: Functional mitral regurgitation (FMR) is the result of an insufficient coaptation of the mitral valve leaflets lacking relevant degeneration or morphological alterations of the valve apparatus. In most patients, this is caused by left ventricular (LV) systolic dysfunction and remodelling (ischemic or non-ischemic). However, a small subset of FMR patients is seen in the context of left atrial (LA) enlargement due to isolated atrial dilation in the absence of a ventricular pathology and has been termed "atrial functional MR" (AFMR) as a distinct etiology of FMR. The effect of transcatheter mitral valve repair (TMVR) by edge-to-edge-repair (e.g., MitraClip®) on AFMR reduction has not been studied, but it is considered to be effective regarding its effect on the anterior-posterior mitral annular diameter. Methods: We retrospectively screened all 737 patients treated with TMVR by edge-to-edge repair in our center between January 2013 and April 2019. AFMR was defined as FMR with: (1) relevant LA dilatation, (2) no LV systolic dysfunction or (3) dilatation, (4) no ischemic etiology of FMR. LA mean pressure was invasively measured peri-interventionally before and after device implantation. Echocardiographic assessment was repeated at 1 year follow-up (1yFUP). Results: Among 350 patients (47.5%) with FMR, 57 patients (16.3%) met the inclusion criteria for AFMR and were included in the data analysis. All patients in the AFMR group (mean age 81.4±5.7 years, 78.9% female) were symptomatic (82.2% functional NYHA class≥III) at baseline and were assessed to be at elevated risk for surgery (mean logistic EuroScore of 24.8±12.0%). TVMR was successfully performed in all patients without any peri-interventional major complications. At hospital discharge, 78.3% of patients had mild residual MR and 17.4% had no detectable MR. At 1 year, the echocardiographic prevalence of residual moderate MR was 11.4% and 2.9% of patients had severe MR (Figure A). Invasive LA mean pressure measurements were available in 39 patients (68.4%). In average, LA mean pressures decreased from 18.8 mmHg to 12.8 mmHg (p<0.001). Analysis at 1yFUP showed a significant reduction in LA volume, both at end-systole (79.6±31.9 vs. 66.9±31.8 ml/m 2 p<0.001; Figure B) and at end-diastole (61.6±21.5 vs. 50.4±27.37 ml/m 2 ; p<0.01; Figure C). LA ejection fraction increased from 18.8%±12.6% to 30.1%±12.3% in 54.8% of patients. These findings were accompanied by a relevant symptomatic benefit (NYHA class I/II was found in 66.7% of patients at 1 year). Conclusions: Transcatheter mitral valve repair by edge-to-edge therapy in symptomatic patients with atrial functional mitral regurgitation is safe and capable of a relevant reduction of mitral regurgitation severity accompanied by symptomatic improvement and positive atrial remodeling. Funding Acknowledgement: Type of funding sources: None.